(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Scientists now investigate medicinal plant-derived natural dyes because they provide sustainable environmentally-friendly options versus synthetic dyes. Environmental concerns regarding synthetic dyes in textile production may find effective answers through the adoption of natural dyes because these colorants originate from renewable resources and avoid the pollution issues related to synthetic dyes. Natural dyes derive from diverse plant-based and animal-based and mineral-based sources since they bypass synthetic manipulation. The biodegradable and low-allergenic and non-toxic nature of natural dyes makes them a superior eco-friendly alternative when compared to synthetic dyes. Natural dyes experienced increased affordability and availability in the textile industry during recent years due to their attractiveness as substitute colorants. Medicinal plants represent a promising natural source of dyes. Bioactive plants yield multiple therapeutic compounds which researchers have identified as hair-coloring pigments for extraction. Various medical plant species continue to demonstrate significant potential as natural dye agents according to multiple research studies. Indigenous plants from different parts of the world display effective color and durability properties when applied to textiles.